1992
DOI: 10.1007/bf00174197
|View full text |Cite
|
Sign up to set email alerts
|

Biocatalysts for production of chiral epoxides

Abstract: An extensive screen for microorganisms capable of growth on olefins was carried out. Over 100 bacterial strains (mesophilic, thermophilic) were isolated in pure culture with gaseous or liquid (internal & terminal) olefins as the sole source of carbon and energy. The organisms included Aero coccus, Aeromonas,Alcaligenes, Flavobacterium, Micrococcus, Moraxella, Nocardia, Pseudomonas, Staphylococcus, Streptomyces and Vibrio spp. and a variety of Gram-negative, Gram-positive and Gram-variable rods/coccobacil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 82 publications
0
9
0
Order By: Relevance
“…Mahmoudian et al have tested 18 organisms that use ethene or propene as the carbon source, including Aerococcus, Alcaligenes, Micrococcus, and Staphylococcus spp., in the epoxidation of short-chain aliphatic olefins, and all of them stereospecifically produce (R)-1,2-epoxypropane (3, 90-96% ee), (R)-1,2-epoxybutane (4, 90-98% ee), and (2R, 3R)-2,3-dimethyloxirane (6, 64-88% ee) from the corresponding olefins (Scheme 13.1) [75]. Other alkene-utilizing bacteria from the genus of Nocardia, Xanthobacter, Mycobacterium, etc.…”
Section: Reactions Catalyzed With Nonheme Iron-dependent Monooxygenasesmentioning
confidence: 99%
“…Mahmoudian et al have tested 18 organisms that use ethene or propene as the carbon source, including Aerococcus, Alcaligenes, Micrococcus, and Staphylococcus spp., in the epoxidation of short-chain aliphatic olefins, and all of them stereospecifically produce (R)-1,2-epoxypropane (3, 90-96% ee), (R)-1,2-epoxybutane (4, 90-98% ee), and (2R, 3R)-2,3-dimethyloxirane (6, 64-88% ee) from the corresponding olefins (Scheme 13.1) [75]. Other alkene-utilizing bacteria from the genus of Nocardia, Xanthobacter, Mycobacterium, etc.…”
Section: Reactions Catalyzed With Nonheme Iron-dependent Monooxygenasesmentioning
confidence: 99%
“…Isolation, characterisation and growth characteristics of the newly isolated ethene-and propene-utilizers have been described previously (Mahmoudian 1989;Mahmoudian and Michael 1992). Cells were routinely grown at 30 ° C in 2-1 flasks containing 400 ml basal mineral-salts medium with ethene or propene (5-10%, v/v) as the sole source of carbon and energy.…”
Section: Methodsmentioning
confidence: 99%
“…These organisms included Aerococcus (M186), Alcaligenes (M101), Micrococcus (M90C) and Staphylococcus (M97B) spp. and a number of Gram-negative, Gram-positive and Gramvariable mesophilic rods/coccobacilli not yet identified (Mahmoudian and Michael 1992). The majority of ethene-and propene-grown cultures (14 organisms) accumulated phenyl glycidyl ether (0.4-1.7 mM) as the sole oxidation product from phenyl allyl ether with specific production rates (non-optimized) in the range 69-323 ixmolh -1 g-1 dry weight.…”
Section: Production Of Phenyl Glycidyl Ether By Alkene-utilizing Bactmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the strain of Aerococcus sp. M186 was reported to catalyze the transformation of propene and 1-butene into the (R)-oxides with 94% ee [105]. Furstoss and co-worker reported that a strain of the fungi Aspergillus niger could diastereoselectively transform (S)-sulcatol derivatives into a single enantiomer of (2S, 5S)-oxides (Scheme 8) [106].…”
Section: Monooxygenase-catalyzed Asymmetric Epoxidation Of Other Subsmentioning
confidence: 99%